Sodobne informacijske tehnologije in storitve: OTS 2017: zbornik dvaindvajsete konference, 13. in 14. junij 2017 - Marina Bajić; Heričko, Marjan; Kous, Katja (2017)
Modern Information Tehnologies and Services: OTS 2017: Proceedings of the Twenty-Second Conference: 13rd- 14th of June 2017. For many decades, the field of Informatics and Information technologies has been the driving force and the enabler for innovations in business and industry, as well in society, improving the quality of life for everyone. Advanced technologies and tools, open standards, interoperability and the increased responsiveness of IS/IT experts are leading the way to the development of intelligent digital service platforms and innovative business models. In these new ecosystems, characterized by active involvement and the engagement of end-users, even competitors are becoming partners and allies. As in previous years, the papers from this year's proceedings address actual challenges and technologies related to the development of advanced software and information solutions, namely BlockChain, BizDevOps, dockers, agile and continuous development, delivery and quality assurance, contactless HCI, Internet of Things, Big Data and Deep learning. We are delighted and thankful to all the authors for their willingness to share their experiences and best practices identified with real-life projects. There is no doubt that the authors have managed to demonstrate not only a successful application of the principles of digital transformation but also the ability to compete on the global market - from Australia, the Philippines, China, Russia, Iran, the EU and Switzerland to the USA.
Keywords: information systems; software; web technologies; information security and privacy; digital transformation